Peran Mediasi Motivasi Kerja : Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT. XYZ: Logistik Kargo Ekspor dan Impor - Abimanyu Adi Nugroho; Henry Eryanto; Maulana Amirul Adha (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to provide new knowledge and insights through analysis on the effect of work discipline and work environment on employee performance, both directly and indirectly through work motivation as a mediating variable, at the import-export logistics company PT XYZ. The method used is with a quantitative approach and causality descriptive design, with SEM-PLS analysis techniques using SmartPLS 4.0. Data were collected through a questionnaire with a total of 129 employee respondents. The results showed that (1) work discipline has no direct effect on work motivation; (2) work discipline has a direct effect on employee performance; (3) work environment has a direct effect on work motivation; (4) work environment has a direct effect on employee performance; (5) work motivation has no direct effect on employee performance; (6) work discipline has no indirect effect on employee performance through work motivation; (7) work environment has no indirect effect on employee performance through work motivation.